(untitled) (International Journal of Environmental Sciences, 2025)
The study aims to examine the impact of servant leadership on turnover intention through psychological empowerment and employee engagement using a multi-mediation model. Data was collected from 211 employees working in multinational organizations in the Delhi-NCR region via a structured questionnaire employing a stratified random sampling method. SPSS 21 and AMOS 24 were used to analyse the data. The findings of the study reflect that in India, servant leadership may not be directly useful in reducing turnover intention; however, it can be diminished when mediated by psychological empowerment and employee engagement.